Optimization of special steel moment frame connection design - Fahmy, Hossam (Kansas State University, 2015)
Special steel moment frames are one of the most common systems used to resist high seismic forces. Well-proportioned moment resisting connections are essential. Special steel moment frame connections must be capable of transferring moment and shear forces that are developed in the beams to the column. These connections must be designed as a highly ductile element in order to dissipate extensive energy thus undergo inelastic deformations. Doubler plates and continuity plates have been recommended by several design codes and standards in order to strengthen the column web and prevent the inelastic deformation of the panel zone due to high shear stress concentrations. However, doubler plates and continuity plates are very expensive due to the large amount of detailing and welding requirements. Furthermore, the extensive welding may affect the properties of the steel in which it may cause shrinkage, lower potential notch toughness and cracking. In any of these cases, there is high potential of losing the desirable inelastic performance required for these SMF. This report investigates the design of the special steel moment frame connections thus eliminating the use of doubler and continuity plates in these connections. Tables are provided that show all steel W-Shape beam sizes with all the adequate steel W-Shape column sizes used in special steel moment frames without the use of doubler and continuity plates in frame connections.
Keywords: Special moment frame connection doubler continuity plates; Architectural engineering (0462)